2008
DOI: 10.1042/bj20080300
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NADPH oxidase 1 in tumour colon epithelial cells

Abstract: In the plasma membrane fraction from Caco-2 human colon carcinoma cells, active Nox1 (NADPH oxidase 1) endogenously co-localizes with its regulatory components p22(phox), NOXO1, NOXA1 and Rac1. NADPH-specific superoxide generating activity was reduced by 80% in the presence of either a flavoenzyme inhibitor DPI (diphenyleneiodonium) or NADP(+). The plasma membranes from PMA-stimulated cells showed an increased amount of Rac1 (19.6 pmol/mg), as compared with the membranes from unstimulated Caco-2 cells (15.1 pm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…In a recent comprehensive descriptive study, Pandey et al (157) reported that Nox5 is present in human saphenous vein and internal mammary artery, cultured human VSMCs, and endothelium, but not in fibroblasts, with the a and b isoforms being most abundant in vascular cells. Adenovirus-mediated overexpression of Nox5 promoted phosphorylation of MAPK in ECs and VSMCs (195), which is similar to our studies in Ang II-stimulated Nox5-containing cells (151,228). These studies, although informative of human Nox expression, have limitations, as they are essentially descriptive and do not reveal much insight into the mechanisms of oxidative stress.…”
Section: Ros and Noxs In Human Vesselssupporting
confidence: 58%
See 1 more Smart Citation
“…In a recent comprehensive descriptive study, Pandey et al (157) reported that Nox5 is present in human saphenous vein and internal mammary artery, cultured human VSMCs, and endothelium, but not in fibroblasts, with the a and b isoforms being most abundant in vascular cells. Adenovirus-mediated overexpression of Nox5 promoted phosphorylation of MAPK in ECs and VSMCs (195), which is similar to our studies in Ang II-stimulated Nox5-containing cells (151,228). These studies, although informative of human Nox expression, have limitations, as they are essentially descriptive and do not reveal much insight into the mechanisms of oxidative stress.…”
Section: Ros and Noxs In Human Vesselssupporting
confidence: 58%
“…Nox1 is abundant in colon epithelium, but is also found in endothelium, smooth muscle, fibroblasts, cardiomyocytes, and microglia (151). It requires p22phox, p47phox (or its homologue NoxO1 [Nox organizer 1]), and p67phox (or its homologue NoxA1 [Nox activator 1]) for its activity.…”
Section: Nox1mentioning
confidence: 99%
“…Despite constituting the main Nox isoform in colon epithelial cells, Nox1 is also associated with production of low levels of O 2 •- in vasculature [25,26]. However, through a complex reaction involving concomitant induction of PKC-, MAPK- and PKA-dependent mechanisms, the vascular pathologies appear to elevate Nox1-mediated release of O 2 •- [27–29] which in turn may trigger BMEC apoptosis to elicit barrier permeability.…”
Section: Discussionmentioning
confidence: 99%
“…78,79 Nox1 requires p22phox, p47phox and p67phox for its activity. It is regulated by the redox chaperone protein disulfide isomerase in vascular smooth muscle cells 80 and has been implicated in vascular smooth muscle cell migration, proliferation and extracellular matrix production, effects mediated by cofilin.…”
Section: Vascular Generation Of Rosmentioning
confidence: 99%